THE TEACHERS' CLINIC. - Garner, S. Paul; Boyd, Ralph L.; Saxe, Emanuel (The Accounting Review, 1948)
Several forms of reconciliation schedule are in general usage. One begins with the balance per bank statement. Reconciling items are then added or subtracted until the final figure equals the balance per check stub. Another form begins with the balance per check stub and ends with the balance per bank statement. A third form shows the difference between the balance per bank statement and the balance per check stub. Then reconciling items are offset one against another until the difference is fully accounted for. A fourth form shows all items related to the records of the bookkeeper for the business in one section and all items related to the records of the bookkeeper for the bank in another section. The reconciling items are added and deducted in their proper sections and the final balances are shown to be in agreement. This is the divided form of reconciliation schedule. In preparing some of the reconciliation forms, students occasionally resort to mal and error methods to secure an agreement. They then find it necessary to search their reconciling items to locate those which require journalization to adjust the bank account balance in their records.